Produção científica nos periódicos de educação na base SciELO (2013-2020): um estudo bibliométrico - Santarpio, Éder José (2024)
Scientific communication is a fundamental part of the knowledge production process, as it is through it that the results of scientific investigations are disseminated. As one of the main means of scientific communication, the journal is responsible for publishing newly generated results validated by a peer review system, which guarantees the quality and reliability of the publication. In this way, the bibliometric approach assumes a fundamental role in the process of analyzing the behavior of scientific production, since, through its analyses, it becomes possible to represent the development of a given scientific field, with its particularities and potentialities. Objectives: Thus, the main objective of the research is to analyze scientific production in the field of Education, examining publications carried out between 2013 and 2020 in specialized journals in the educational area. And as specific objectives: Prepare a brief history of the six periodicals that make up the research corpus.; map, through the bibliometric approach, scientific production in the field of Education, identifying institutions, regional and international distribution of affiliations; identify how bibliographic production is organized in relation to authorship and co-authorship in the field of Education; analyze the profile of authors in relation to gender in the field of Education; Identify the themes studied in the texts published in the analyzed journals; identify the use of other languages in texts published in the journals analyzed; verify the applicability of Lotka's law in the educational field. Methods: According to the objectives, the research will adopt a qualitative and quantitative approach with the bibliometric approach as an analysis tool. Briefly, the research was developed in seven distinct phases: Preparation of the theoretical framework; development of the collection protocol; data collect; construction of bibliometric indicators (articles and authorship); storage, description and processing of data; contextualization of periodicals; analysis and interpretation of results. Results: Among the results obtained, the following stand out: Growth of scientific production in the field of Education. Growth in the publication of texts in other languages, mainly in English, adherence to publishing texts in another language by researchers working in the field of Education. Furthermore, it was possible to identify that the research published in the journals analyzed reflects a thematic diversity, which demonstrates the scientific scope of the educational field. Regarding the gender of the authors, it was possible to identify that the majority of authors are female. However, the analysis demonstrated that there is a considerable tendency for scientific collaboration through female-only co-authorship. Regarding geographic distribution (national and international), it is noted that there is a geographic concentration, that is, regions and countries with a large number of institutional vehicles. Regarding national institutions, the vast majority of links are located in the southeast region, mainly in the state of São Paulo. The analysis of the productivity of the authors demonstrated that there is no concentration of large producers of studies and when applying Lotka's law to the journals analyzed, it was possible to identify that 70.7% (n=3,318) of the authors had only one contribution, which differs from the 60% provided for by law. Conclusion: It is possible to conclude, even with all the historical issues that permeate the development of research in the field of Education, that educational research published in journals reflects thematic, geographic and institutional diversity, demonstrating, therefore, the breadth and depth of research coming from the field of Education.